Endocarditis caused by anaerobic bacteria. (October 2017) - Kestler, M.; Muñoz, P.; Marín, M.; Goenaga, M.A.; Idígoras Viedma, P.; de Alarcón, A.; Lepe, J.A.; Sousa Regueiro, D.; Bravo-Ferrer, J.M.; Pajarón, M.; Costas, C.; García-López, M.V.; et al.
Abstract: Background: Infective endocarditis (IE) caused by anaerobic bacteria is a rare and poorly characterized disease. Most data reported in the literature are from case reports [1–3]. Therefore, we assessed the situation of anaerobic IE (AIE) in Spain using the database of the Spanish Collaboration on Endocarditis (GAMES). Methods: We performed a prospective study from 2008 to 2016 in 26 Spanish centers. We included 2491 consecutive cases of definite IE (Duke criteria). Results: Anaerobic bacteria caused 22 cases (0.9%) of definite IE. Median age was 66 years (IQR, 56–73), and 19 (86.4%) patients were men. Most patients (14 [63.6%]) had prosthetic valve IE and all episodes were left-sided: aortic valves, 12 (54.5%); and mitral valves, 8 (36.4%). The most common pathogens were Propionibacterium acnes (14 [63.6%]), Lactobacillus spp (3 [13.63%]), and Clostridium spp. (2 [9.0%]), and the infection was mainly odontogenic. Fifteen of the 22 patients (68.2%) underwent cardiac surgery. Mortality was 18.2% during admission and 5.5% after 1 year of follow-up. When patients with AIE were compared with the rest of the cohort, we found that although those with AIE had a similar age and Charlson comorbidity index, they were more likely to have community-acquired IE (86.4% vs. 60.9%, p = 0.01), have undergone cardiac surgery (68.2% vs 48.7% p = 0.06), and have had lower mortality rates during admission (18.2% vs. 27.3%). Conclusion: IE due to anaerobic bacteria is an uncommon disease that affects mainly prosthetic valves and frequently requires surgery. Otherwise, there are no major differences between AIE and IE caused by other microorganisms. Highlights: Prospective evaluation of the current situation of Anaerobic Infective Endocarditis nationwide. Most common pathogens were Propionibacterium acnes, Lactobacillus spp and Clostridium spp. Anaerobic infective endocarditis is an uncommon disease that affects mainly prosthetic valves.